(untitled) (IIUC Studies, 2018)
Transmucosal buccal drug delivery system is considered as a future drug delivery technology, always assist to enhance patient compliance mainly for paediatric and geriatric community. The studies aim to develop buccal delivery for delivering a hydrophilic drug, flucloxacillin sodium, across the mucosal route. The buccal films are comprised of a bio-adhesive polymer, plasticizer and drug. Optimised films were characterised by measurement of weight, length and width, hardness, thickness, surface pH, moisture content and uptake, swelling study, folding resilience, hydration and entrapment efficiency. Drug release studies were performed for different polymer-plasticizer-drug ratios. Concentration of polymer and plasticizer were influenced on the development, evaluation and release rate of flucloxacillin sodium from the buccal films. In conclusion, these studies reveal that buccal delivery of flucloxacillin sodium can be an alternative route in comparison to conventional route for patient compliance. IIUC Studies Vol.14(1) June 2017: 09-20